PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - petty arisanti arisanti (Jurnal Akuntansi dan Keuangan (JAK), 2022)
The purpose of this study was to analyze the effect of capital structure on firm value in manufacturing companies on the Indonesia Stock Exchange. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange with a research period of 2017, 2018, 2019 and 2020. The sample was selected using a purposive sampling method with a total of 20 companies. The data was obtained based on the publication of the Indonesia Stock Exchange (IDX). The variables used are capital structure as the independent variable, firm value as the dependent variable. Testing the first hypothesis, the effect of capital structure on firm value using simple linear regression. Testing the second hypothesis, the effect of capital structure on firm value with profitability as a mediator using linear regression. Testing the research hypothesis using a model test technique (path analysis) with the application tool SPSS (Statical Product and Service Solutions) version 21. The results of this study prove that the capital structure has a positive and significant effect on firm value.